After hours presentation of traumatic dental injuries to a major paediatric teaching hospital. (June 2014) - Warren, M; Widmer, R; Arora, M; Hibbert, S
Abstract Background Thorough record taking of traumatic dental injuries is vital. This study aimed to assess the efficacy of a structured paper history for this purpose. Furthermore, the aetiology and epidemiology of these injuries were investigated, with the aim of formulating appropriate preventive guidelines. Methods A six‐month audit of traumatic dental injuries presenting after hours was undertaken at The Children's Hospital at Westmead. A structured paper history form was subsequently created, and the data collected over the following 12 months. Results Structured paper histories assisted in thorough record taking. Over 12 months, 190 paediatric patients (male:female ratio 1.5:1) were treated after hours with traumatic dental injuries. There were 396 injured teeth among 182 patients (eight patients had soft tissue injuries only). The mean number of injured teeth per patient with dental injuries was 2.18, the vast majority being maxillary central incisors (62% of primary teeth and 66% of permanent teeth). The most common cause was 'accident during play', followed by a fall. The severe injuries, avulsions and luxations, comprised 63% of injuries to primary teeth and 26% to permanent teeth. Conclusions Structured paper histories are useful for recording traumatic dental injuries. The vast majority of these injuries are due to unavoidable accidents, rendering their prevention challenging from a public health perspective.